Occult Renal Calcifications in Patients with Normocalcemic Primary Hyperparathyroidism and Their Association with the Parathyroid Hormone-Vitamin D Axis - Fernanda Victor; Alyne Layane Pereira Lemos; Anna Mirella de Holanda Ribas; Leonardo Bandeira; José Henrique Pimentel; Luiz Otávio de Andrade Damázio; Francisco Bandeira (International Journal of Endocrinology)
Normocalcemic primary hyperparathyroidism (NPHPT) is characterized by elevated serum levels of parathyroid hormone (PTH) with persistently normal serum calcium concentrations after excluding secondary causes of hyperparathyroidism. Urolithiasis and/or nephrocalcinosis may occur in hypercalcemic PHPT, but little is known about these complications in NPHPT. Objectives. To identify occult urolithiasis and nephrocalcinosis in asymptomatic patients with NPHPT and evaluate biochemical markers as risk predictors for the development of renal calcification (RC). Methods. Cross-sectional analysis of 34 patients with no history of urolithiasis and/or nephrocalcinosis. The diagnosis of NPHPT was as follows: elevated serum PTH (reference range: 15–65 pg/mL), normal albumin-corrected serum calcium, normal urinary calcium excretion, serum 25(OH)D >30 ng/mL, eGFR (CKD-EPI) > 60 mL/min/1.73 m2, without intestinal disease, and not on medications such as thiazide diuretics, lithium, bisphosphonates, or denosumab. Patients were categorized according to the presence or absence of RC identified by renal imaging. Their clinical and biochemical characteristics were then compared. Results. The patients had a mean age of 67.97 ± 10.45 years, predominantly postmenopausal women (88.2%); serum PTH, 119.67 ± 64.44 pg/mL; 25(OH)D, 39.00 ± 8.88 ng/dL; 1.25(OH))2D, 74.53 ± 26.37 pg/mL; corrected serum calcium, 9.34 ± 0.62 mg/dL; and 24-hour urinary calcium, 134.87 ± 79.68 mg/day. RC was identified in 26.5% of the patients. There was no difference in anthropometric and clinical parameters, renal function, 25(OH)D, and urinary pH in patients with or without RC. Patients with RC had higher PTH values (176.22 vs. 99.32 pg/mL, P = 0.001), 1.25(OH) 2D (96.83 vs. 62.36 pg/mL, P = 0.005), and 24-hour urinary calcium (181.9 vs. 117.94 mg/day, P = 0.037). Conclusion. Occult renal calcifications are common in NPHPT and are associated with increased serum PTH, 1.25(OH))2D, and 24 h urinary calcium.